The effectiveness of using audiobooks to develop pronunciation skills to speak with an appropriate intonation, at University of El Salvador on the students of english pronunciation subject, semester I-2020 - Santamaría Alvarenga, Karla Estefany
Nowadays, the majority of the people do not take the time to practice very often their pronunciation skills and they get used to make some mispronunciations; especially, foreign language students. So this research study helps to recognize this common situation on second language learners at the University of El Salvador. In addition to this, the primary goal of this study research is to know the effectiveness of using audiobooks on English pronunciation students and see the development of their English skills and improvements they can make after using them. Besides that, this research work is experimental because it required an experiment control to see if there is an improvement on student's pronunciation before & after using an audiobook. Therefore, important results were found after using an audiobook where some improvements where identified on the second language learners which lend us to think that Audiobooks can be the perfect tool that facilitates the pronunciation for their pronunciation for foreign languages students at the University of El Salvador.